AUTOMATED DECISION MAKING IN ADMINISTRATIVE PROCEDURE – MYTH OR REALITY? - Zoran R. Jovanovic,; Andonović, Stefan (NBP. Nauka, bezbednosti, policija, 2021)
In this paper the authors analyze the possibility of automated decision making in the administrative procedure, as one of the aspects of the development of e-administration. Services of e-administration are developing and expanding to numerous aspects of administrative work, with administrative decision-making being one of the most important and intriguing aspect. Having that in mind, the authors defined the term automated decision making and researched the question whether the legal framework of the Republic of Serbia enables the implementation of new, digital forms of administrative decision making. For that purpose, relevant provisions of the Law on General Administrative Procedure, the Law on Electronic Government and the Law on Personal Data Protection have been analyzed. The authors identified the situations of general administrative procedure within which it would be possible to consider practically, and in the near future normatively as well, the introduction of an automated decision making in the administrative procedure. A lesser portion of the paper is dedicated to the prerequisites and risks related to human rights and liberties when it comes to automated decision making in the administrative procedure.
Keywords: e-administration, administrative procedure, administrative decision making, automated decision making.